Analisis Teori Keputusan Pembelian Kotler & Keller: Peran Influencer dalam Membentuk Perilaku Fast Moving Skincare pada Generasi Z melalui Media Sosial Instagram - Aisyah Putri Balqis; Chrisdina Chrisdina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This research examines the role of influencers in shaping Fast Moving Skincare consumption behavior among Generation Z on Instagram, against the backdrop of rapid beauty product proliferation that drives trend-responsive purchasing patterns. Drawing on Kotler and Keller's (2009) consumer decision-making theory, this study employs a descriptive qualitative approach through in-depth interviews with four informants — beauty community members and active skincare users. The findings reveal that influencer impact is not uniform across all stages of the decision-making process. At the problem recognition stage, Generation Z relies primarily on personal experience and close social circles rather than influencer content. Influencers become relevant at the information search stage, functioning as visual and interactive reference points, though audiences apply active filtering throughout. At the alternative evaluation stage, peer influence from close social circles outweighs influencer recommendations. This finding points to an additional stage not accounted for in the original Kotler and Keller model: the influence of close social environments immediately before the purchase decision. Generation Z's purchasing behavior, taken as a whole, remains selective and is not straightforwardly driven by digital trends.